Environmental education and elementary school students’ behavior in green schools; Applying TPB Theory - Hadis Esmaeili; Samaneh Sanjabi; Shahpar Geravandi (Environmental Resources Research, 2022)
The goal of this study was to analyze the environmental behavior of elementary school students in green schools using Ajzen theory of planned behavior (TPB). This quantitative study was conducted through a cross-sectional descriptive survey and using a questionnaire created by the researcher. The study had a statistical population of 229 elementary students. One hundred students were selected as the sample based on the table by Krejcie and Morgan. The data collected were analyzed using SPSS and AMOS software through Path Diagram Analysis. The findings indicated that attitude, subjective norms, and perceived behavioral control (self-efficiency) had a positive and significant association with intention. However, there was no significant relationship between intention and frequency of environmental behavior. The finding in this model suggest that other undiscovered factors may be involved in environmental behavior. Modifying the three components of attitude, subjective norms, and perceived behavioral control will therefore lead to the development and enhancement of intention for environmental behaviors. Other effective factors on environmental behavior, however, should be explored in further studies to minimize environmental damage and modify the course of environmental damage.